Predictive Significance of Thymidylate Synthase Expression in Non-small Cell Lung Cancer - Kulda, Vlastimil; Hrda, Kristyna; Houdek, Zbynek; Dobra, Jana Kolaja; Vrzakova, Radana; Svaton, Martin; Safranek, Jarmil; Dolezal, Jan; Babuska, Vaclav; Pesek, Milos; Topolcan, Ondrej; Pesta, Martin (Anticancer research, 2017)
BACKGROUND/AIM: To date, many studies have suggested that thymidylate synthase (TS) could be used as a prognostic and predictive marker in non-small cell lung cancer (NSCLC) patients. However, results have been contradictory. The aim of this study was to evaluate TS mRNA levels in tumor tissue of NSCLC patients who underwent complete surgical resection and to analyze its prognostic and predictive potential. MATERIALS AND METHODS: The study group consisted of 64 patients who underwent curative lung resection. Paired lung tissue samples were taken directly from the tumor tissue and from adjacent, histologically cancer-free lung tissue. The quantitative estimation of TS expression was performed by reverse transcription real-time polymerase chain reaction (RT-qPCR). The relationship between TS expression level and disease-free interval (DFI) and overall survival (OS) was analyzed. RESULTS: There was significantly higher TS expression in NSCLC tumor tissue comparing to normal lung tissue. In the group of patients who received adjuvant chemotherapy based on platinum derivatives in combination with paclitaxel or gemcitabine, we found shorter DFI (p=0.0473) and OS (p=0.0053) in those with high expression of TS. CONCLUSION: Our results demonstrated the relationship of high tumor tissue TS levels to adverse prognosis in patients undergoing adjuvant chemotherapy. TS is a non-specific tumor marker with respect to NSCLC, therefore we think that its best use would be as a member of the panel of predictors of adjuvant treatment efficacy.
Keywords: nádory plic; thymidylátsynthasa; nemalobuněčný karcinom plic; Thymidylate Synthase; Lung Neoplasms; regulace genové exprese u nádorů; Humans; Thymidylate synthase; lidé středního věku; Carcinoma, Non-Small-Cell Lung; Biomarkers, Tumor; Chemotherapy, Adjuvant; Female; Aged; protokoly protinádorové kombinované chemoterapie; výsledek terapie; senioři; lidé; adjuvantní chemoterapie; nádorové biomarkery; ženské pohlaví; Kaplanův-Meierův odhad; Male; NSCLC; Middle Aged; prognóza; Antineoplastic Combined Chemotherapy Protocols; Treatment Outcome; Kaplan-Meier Estimate; mužské pohlaví; Gene Expression Regulation, Neoplastic; prognosis; Prognosis